PENGARUH PENAMBAHAN TEPUNG DAUN SINGKONG (Manihot utillisima) PADA PENDEDERAN IKAN LELE DUMBO (Clarias gariepinus) UNTUK MENINGKATKAN PERTUMBUHAN DAN SINTASAN - Herianto, Herianto; Mustarin, Amirah; Patang, Patang (Jurnal Pendidikan Teknologi Pertanian, 2019)
Feed in the cultivation of catfish become the main factor affect the success of cultivation. This study aims to reveal and survival of nursery thorugh adding leaf cassava dust to feed. This study uses a T test (one sample T test) to compare treatments with the provision of organic feed and commercial feed consisting of 3 replications. The dose of feeding is 3% of the weight of the fish for 30 days of maintenance with the frequency of feeding twice a day. Parameters observed included weight growth and survival as well as temperature, pH, DO and NH3 of catfish. The results showed that the provision of organic feed in the African catfish nursery did not have an effect on the parameters of weight growth and survival. Overall treatment of feed with the addition of cassava leaf flour supports catfish growth which can be seen in the growth of catfish weight which increases during maintenance.